El acceso a fuentes abiertas al conocimiento en ciencia y tecnología en América Latina y el Caribe - Ayuso García, Mª Dolores; AYUSO SÁNCHEZ, Mª José (Revista General de Información y Documentación, 2010)
This article presents a wide and comprehensive study that analyzes the impact of the access to knowledge sources in order to disseminate scientific and technological activities in emerging and developing countries, from the perspective of social inclusion. Social inclusion is defined as the use of ICT and its potential in the process of creating technological tools that promote collaborative work in virtual learning environments. The access to knowledge sources is shaping a digital literacy process that guarantees the production of digital resources in the context of information networks. Projects of diffusion of scientific knowledge in virtual learning environments in emerging and developing countries are also analyzed. In the area of Latin America and the Caribbean in particular, initiatives to design an infrastructure for the . promotion of science and technology are reviewed. The creation of the Advanced Networks for Science, Technology, Education and Innovation is studied. The article emphasizes the study of collaborative learning environments as an asset for the digital literacy in the process of scientific communication. The contribution of the concept of Web 2.0 to collaborative and open environments of informational learning is reviewed, through networks and projects as open access platforms to knowledge.